Evaluation of AMPLILINK Software for the COBAS AMPLICOR System - Kessler, Harald H. (American Society for Microbiology, 1999)
The use of AMPLILINK version 1.0 software was evaluated for the operation and control of one COBAS AMPLICOR instrument and for two COBAS AMPLICOR instruments run simultaneously to perform and detect nucleic acid amplification reactions. A total of 3,384 results were analyzed. The initial accuracy of the results was 99.91%. Three errors of omission of transfer of data from the COBAS AMPLICOR to the AMPLILINK system were observed. Two of these errors were from a single specimen, where both the analyte and internal control results were not transmitted. These errors did not interfere with the correctness of any other data. There were no interruptions of runs, and no data were mixed. AMPLILINK increased convenience, saved labor, and was found to be a very useful addition for clinical laboratories performing molecular-diagnostic procedures with the COBAS AMPLICOR system.